Different Treatment Bagi Eksil Korban Peristiwa 1965 di Eropa - Yohanes Victor Baro Bitan Lamatokan; Robertus Wijanarko (International Forum of Researchers and Lecturers, 2024)
This article examines the differential treatment of so-called exiles, people who were sent abroad either to study or to work. During the events of 1965-1966, their passports were revoked. They lived by moving from one country to another in search of a